2000
DOI: 10.1097/00002281-200009000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Update in Sjögren syndrome

Abstract: Sjögren syndrome (SS), the second most common autoimmune rheumatic disease, refers to keratoconjunctivitis sicca and xerostomia resulting from immune lymphocytes that infiltrate the lacrimal and salivary glands. However, differential diagnosis remains confusing due to the high prevalence of vague symptoms of dryness, fatigue, and myalgias in the general population. The problems of diagnosis are further compounded by the finding of "positive" antinuclear antibodies in a high percent of the general population. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
118
0
20

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 233 publications
(139 citation statements)
references
References 87 publications
1
118
0
20
Order By: Relevance
“…Diseases characterized by major deficits in lacrimal gland function range in severity from keratoconjunctivitis sicca (dry eye) to the autoimmune disease, Sjö gren's syndrome. 18,19 As well, the dryness associated with decreased corneal sensation and concomitant reduction in tear flow following refractive surgery can complicate corneal recovery. 20 Since preservation of tear production and release is essential for ocular health, we questioned whether exposure to Ad would alter the functioning of this essential gland.…”
Section: Introductionmentioning
confidence: 99%
“…Diseases characterized by major deficits in lacrimal gland function range in severity from keratoconjunctivitis sicca (dry eye) to the autoimmune disease, Sjö gren's syndrome. 18,19 As well, the dryness associated with decreased corneal sensation and concomitant reduction in tear flow following refractive surgery can complicate corneal recovery. 20 Since preservation of tear production and release is essential for ocular health, we questioned whether exposure to Ad would alter the functioning of this essential gland.…”
Section: Introductionmentioning
confidence: 99%
“…However, the precise mechanisms of human autoimmune diseases remain unclear, and this prevents the establishment of specific therapeutic strategies for these conditions. Sjögren's syndrome (SS) is an autoimmune disease characterized by the destruction of lacrimal and salivary glands, resulting in dry eyes and dry mouth as the major symptoms (10). Because SS patients have high titers of autoantibodies, including anti-SSA/Ro and SSB/ La, abnormal T and B cell activation has been considered to cause SS (10,11).…”
mentioning
confidence: 99%
“…Sjögren's syndrome (SS) is an autoimmune disease characterized by the destruction of lacrimal and salivary glands, resulting in dry eyes and dry mouth as the major symptoms (10). Because SS patients have high titers of autoantibodies, including anti-SSA/Ro and SSB/ La, abnormal T and B cell activation has been considered to cause SS (10,11). We have established and investigated an animal model of SS in NFS/sld-mutant mice thymectomized 3 days after birth and found that the 120-kd ␣-fodrin protein is a critical autoantigen in the development of SS in this mouse model (12)(13)(14).…”
mentioning
confidence: 99%
See 2 more Smart Citations